The Impact of the Implementation of the Independent Learning Policy on the Governance Performance of SMP Negeri 1 Karangtengah, Cianjur Regency - Agus Setiawan; Yeti Rohayati; Diani Indah (Global Education Journal, 2026)
Education has a strategic position in national development because it is the main instrument in shaping the quality of human resources. This study examines the effect of Merdeka Belajar policy implementation on school governance performance at SMP Negeri 1 Karangtengah, Cianjur Regency. The study was motivated by the importance of school capacity in translating educational policy into effective institutional governance. This research used a quantitative approach with an explanatory design. The population consisted of all educators and education personnel at SMP Negeri 1 Karangtengah, totaling 55 respondents, and the sampling technique used was total sampling. Data were collected through questionnaires using a five-point Likert scale. The data were analyzed using descriptive analysis, simple linear regression, correlation coefficient, determination coefficient, and t-test. The results showed that both Merdeka Belajar policy implementation and school governance performance were in the moderate category. The regression analysis showed that Merdeka Belajar policy implementation had a positive and significant effect on school governance performance, with a regression coefficient of 0.725, a correlation coefficient of 0.872, and a coefficient of determination of 0.760. These findings indicate that 76.0% of school governance performance is explained by Merdeka Belajar policy implementation.